(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Antioxidant activity of ethyl acetat extraction of creeping thyme, growing in the regions with various altitude above the sea level, was investigated. In the paper is demonstrated that the highest amount of antioxidants (14.06%) is in ethyl acetat extraction of creeping thyme, growing at the altitude of 650 m a.s.l., where the temperature under the sun is above 30°C. It was found as well, that from the studied solvents the best extractant for antioxidants of creeping thyme is the solvent with the greatest polarity (acetone).